Speculative bubble in the China stock market. - Tan, Yi Lee. (2008)
The aim of our research paper is to investigate the presence of a speculative bubble in the China stock market in midst of the rising stock prices. Empirical tests based on excess volatility; stationarity and cointegration will be carried out for our investigation. Limitations and biases of our tests will also be discussed.